The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41598-020-70118-7
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of human papillomavirus-related oropharyngeal cancer in a classically low-burden region of southern Europe

Abstract: The incidence of human papillomavirus (HPV)-related oropharyngeal cancer is increasing in some regions. Nevertheless, the epidemiology of this disease has not been extensively investigated in southern europe. We conducted a retrospective cohort study of patients diagnosed with primary oropharyngeal cancer from 1991 to 2016. Cancer tissues underwent histopathological evaluation, DNA quality control, HPV-DNA detection and p16 INK4a immunohistochemistry. Data were collected from medical records. Factors associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 38 publications
0
15
1
2
Order By: Relevance
“…Previous studies also showed less favorable survival of p16 + /HPV DNA − cases. 8 , 9 , 10 , 11 , 12 , 13 However, information on the prognostic value of p16 + /HPV DNA − OPSCC is limited, especially in Asian populations. To our knowledge, only one study on Japanese patients showed that p16 + /HPV DNA − cases displayed OS similar to that of p16 + /HPV DNA + cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies also showed less favorable survival of p16 + /HPV DNA − cases. 8 , 9 , 10 , 11 , 12 , 13 However, information on the prognostic value of p16 + /HPV DNA − OPSCC is limited, especially in Asian populations. To our knowledge, only one study on Japanese patients showed that p16 + /HPV DNA − cases displayed OS similar to that of p16 + /HPV DNA + cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, a subset of HPV‐positive patients, determined using this method, have poor outcomes. 8 , 9 , 10 , 11 , 12 , 13 Therefore, it is imperative to refine tools for improved risk stratification of HPV‐positive patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…están infectadas por el VPH y 14 millones se infectan cada año. En el sur de Europa las estimaciones actuales de la prevalencia del VPH son relativamente bajas (9-24%) 3,4 .…”
Section: Vacunologíaunclassified
“…Since the discovery that a subset of oropharyngeal cancers is related to the human papilloma virus (HPV), the knowledge about this unique entity has grown exponentially, [1][2][3] and the incidence is continually increasing worldwide. [4][5][6][7] In addition, due to the observation of a biologically distinct and favorable natural history and excellent response to therapy for HPV-related cancers, a separate staging system has been introduced for these tumors in the latest edition of the American Joint Committee on Cancer (AJCC eighth Ed). 8,9 2 | Rationale for a specific HPV-related oropharynx cancer staging system There are multiple facts that led to the development of a separate staging system for HPV-positive tumors.…”
Section: Introductionmentioning
confidence: 99%